Psychologycal Support Program “Rehabilitation And Stress Disorders” : A Literature Review - Azzahra, Alifia Rizqyandra; Testania, Nabila; Maulina, Rimala; Setyawan, Muhammad Sony (Tarqabin Nusantara Group, 2024)
Introduction: A disaster is where a situation is most avoided, after a disaster everywhere it is, it must have a critical impact on the environment, one of which is a society that is affected by a disaster. Generally, after a disaster, the victims are exposed to stress and some of the mental disorders caused by the disaster,The government is aware of the effects of disasters, especially on the mental, umumnya after disasters, the government provides a special place for those with trauma and stress. in this study using a method of study of literature. In the results of the literature study, the government conducts first aid or (PFA) with the first aid of the community, with this policy, hopefully the community will be calmer and more comfortable after a disaster.